Serum pigment epithelium-derived factor levels are increased in patients with biopsy-proven nonalcoholic fatty liver disease and independently associated with liver steatosis - EREN, FATİH; YILMAZ, YUSUF (ELSEVIER SCIENCE BV, 2011)
Background: Increased serum concentrations of pigment epithelium-derived factor (PEDF) have been linked to the metabolic syndrome in the general population. However, the relationship between serum PEDF and nonalcoholic fatty liver disease (NAFLD), a hepatic manifestation of the metabolic syndrome, remains unknown. Methods: We assayed serum PEDF levels in 156 patients with biopsy-proven NAFLD and 103 nonsteatotic control subjects who were matched for age and sex. The association between levels of PEDF and clinical, biochemical, and histological phenotypes was examined. Results: NAFLD patients had significantly higher serum PEDF levels (1.97 +/- 0.50 mu g/mL) than control subjects (1.51 +/- 0.49 mu g/mL, Student's t test, P<0.001). Multivariable-adjusted stepwise regression analysis showed that PEDF ([beta] = 0.32, t = 3.13, P = 0.002) and triglycerides ([beta] = 0.22, t = 2.23. P = 0.02) were, in the order they entered into the model, the main independent predictors of steatosis scores in our patients with NAFLD. Conclusions: Serum PEDF levels are significantly increased in patients with biopsy-proven NAFLD and are associated with liver steatosis independently of traditional risk factors. (C) 2011 Elsevier B.V. All rights reserved.
Keywords: Pigment epithelium-derived factor; Nonalcoholic fatty liver disease; Enzyme-linked immunosorbent assay; Steatosis; ENDOTHELIAL GROWTH-FACTOR; FACTOR PEDF; METABOLIC SYNDROME; INSULIN-RESISTANCE; ANGIOGENESIS; ACTIVATION; CELLS